2020
DOI: 10.21203/rs.3.rs-42426/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation and Starch Characterization of Non-Transgenic BEI and BEIIb Double Mutant Rice (Oryza sativa) with Ultra-high Level of Resistant Starch

Abstract: Background Cereals high in resistant starch (RS) are gaining popularity, as their intake is thought to help manage diabetes and prediabetes. Number of patients suffering from diabetes is also increasing in Asian countries where people consume rice as a staple food, hence generation of practically growable high RS rice line has been anticipated. It is known that suppression of starch branching enzyme (BE) IIb increases RS content in cereals. To further increase RS content and for more practical use, we generat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Previous studies reported an increase of amylose in some mutant rice lines. For example, the apparent amylose content of ss3a be2b 26) and be1 be2b 29) is 45.1 % and 51.7 %, respectively, which is higher than that of the be2b single mutant 26) (28.1 %). The reason for this is that loss of SS and BE increases GBSSI expression levels.…”
Section: Apparent Amylose Contentmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies reported an increase of amylose in some mutant rice lines. For example, the apparent amylose content of ss3a be2b 26) and be1 be2b 29) is 45.1 % and 51.7 %, respectively, which is higher than that of the be2b single mutant 26) (28.1 %). The reason for this is that loss of SS and BE increases GBSSI expression levels.…”
Section: Apparent Amylose Contentmentioning
confidence: 80%
“…14) The increased amylose content in these mutant rice lines can be explained by the reduction of amylopectin biosynthesis resulting in leftover ADP-glucose as a substrate, and GBSSI was able to use ADP-glucose for amylose synthesis. 14) The seed weight of double mutant lines lacking SS and BE isozymes, such as ss3a be2b, 26) ss1 L be2b, 28) and be1 be2b, 29) is greater than that of the be2b single mutant line.…”
Section: Apparent Amylose Contentmentioning
confidence: 98%
“…Starch is the main energy-reserve polysaccharide in cereal crops, and is the chief source of carbohydrates in the human diet (Amagliani et al, 2016). Starch also has many technological, medical, and industrial uses (Miura et al, 2021). Rice starch is mainly composed of two biopolymers: amylose and amylopectin.…”
Section: Introductionmentioning
confidence: 99%
“…Amylopectin is a branched glucose polymer and is mainly synthesized via concerted reactions catalyzed by three types of biosynthetic enzymes: starch synthases (SSs), starch branch enzymes (SBEs), and debranching enzymes (DBEs; Wang et al, 2017). Among these enzymes, mutations in the SBE isozymes showed significant association with amylose content variation (Nishi et al, 2001;Satoh et al, 2003;Butardo et al, 2011;Yang et al, 2012;Kim et al, 2018;Adeva et al, 2020;Miura et al, 2021). In rice, three isoforms of SBE are present: BEI (SBE1 or BE1), BEIIa (SBE4 or BE2a), and BEIIb (SBE3 or BE2b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation